Vocabulário da pandemia do novo coronavírus: uma proposta de análise discursiva sobre a produção e efeitos de sentido das palavras em tempos de emergência sanitária - Ribeiro, Gabriela Gonçalves (2024)
The Vocabulary of the new coronavirus pandemic was developed by 26 researchers from different institutions, united with the purpose of creating pandemic entries that recorded the words that most circulated in the media during the period from 2020 to 2023. This collaborative work, based on shared authorship (BIAZUS, 2015) and inspired by the concept of sharing the sensitive coming from Rancière (2005), it aims to take quality information beyond the university's concealment, preserving the meanings of words and preventing them from being forgotten. Based on this, this dissertation presents the investigation of the effects and production of meaning in some pairs of entries in the Vocabulary of the new coronavirus pandemic, comparing them with other linguistic instruments. To this end, we will mobilize the theoretical and methodological apparatus of French Discourse Analysis in its relations with the History of Linguistic Ideas. The pairs analyzed are “inequality – fear”, “perspective – narrative”, “genocide and pandemic” and “field hospital – resistance”. The selected entries show us the movements of meaning between paraphrase and polysemy, between the same and different that the pandemic production conditions provided. The pairs of words were constructed by us, they establish relationships of meaning with each other within the Vocabulary of the new coronavirus pandemic, their meanings are in contact, whether through a word or the definition presented in the vocabulary. We found that the conditions of production of the health emergency brought possible other meanings, introducing the new and establishing yet another link in the construction of the discursive memory that signals what the pandemic we are experiencing is and, soon, what it was.